Air Frosts in Poland in the Thermal Growing Season (AT > 5 °C) - Czesław Koźmiński; Agnieszka Mąkosza; Jadwiga Nidzgorska-Lencewicz; Bożena Michalska (Agriculture, 2023)
Frosts cause damage to plants in field crops and also trees, thus contributing to heavy economic losses in agriculture. One of the consequences of climate warming is the lengthening of the thermal growing season (AT > 5 °C) and acceleration of phenological phases as well as the lengthening of the frost-free period. This favourable element allows the extension of the range of cultivated plants to include plants requiring warmth and a longer development period. The present study concerns the area of Poland. The data on mean and minimum 24-h period air temperature (200 cm above ground level) were obtained from 52 meteorological stations of the Institute of Meteorology and Water Management—National Research Institute (IMGW-PIB) for the period 1971–2020. A day with air frost was identified when the recorded minimum air temperature was below 0.0 °C and the mean 24-h period air temperature was above 0.0 °C. All calculations concerning frosts were limited to the period with mean 24-h period air temperature >5 °C (the growing season) as determined with the Gumiński method. The obtained results show that in the thermal growing season (AT > 5 °C) in Poland, no statistically significant change in the average number of days with air frosts in the period 1971–2020 was found. On average, in Poland, in the years 1971–2020, a lengthening of the thermal growing season by 6.2 days over 10 years was identified. Earlier disappearance of the latest air frosts in spring was identified as 2 to 3 days over 10 years, and the later occurrence of air frosts in autumn as 1 to 4 days over 10 years. The share of severe (−4.1°C ÷ −6.0 °C) and very severe (<−6.0 °C) frosts in the total number of days with air frosts in Poland amounts to, on average, 5.8% in spring and 2.6% in autumn.